Trust yourself, discover your resilience! From self-efficacy to life satisfaction: the mediating effect of psychological resilience - Karababa, Burak; Aydin, Gokcer; Yilmaz, Oguzhan; Akkus, Yavuz; Bayram, Esra; Aydin, Gokhan (Frontiers in Psychology, 2025)
IntroductionThis study investigates the mediating role of psychological resilience in the relationship between self-efficacy and life satisfaction among student athletes. Self-efficacy and psychological resilience are considered key psychological resources that can enhance overall well-being and life satisfaction, particularly in the context of sports.MethodsThe research was conducted using a quantitative design. The sample consisted of 481 student athletes (223 male, 46.4%; 258 female, 53.6%) studying at faculties of sport sciences in various universities across Turkey. Data were collected through the General Self-Efficacy Scale, the Brief Resilience Scale, and the Life Satisfaction Scale. Statistical analyses were performed using SPSS 27.0 and the PROCESS Macro (Model 4). Pearson correlation analysis was used to examine relationships between variables, followed by mediation analyses based on hierarchical regression and bootstrap methods.ResultsFindings indicated that self-efficacy significantly and positively predicted psychological resilience (β = 0.517, p < 0.001). Both self-efficacy (β = 0.278, p < 0.01) and psychological resilience (β = 0.141, p < 0.01) were significant predictors of life satisfaction. Mediation analysis revealed that psychological resilience partially mediated the relationship between self-efficacy and life satisfaction (β = 0.073, 95% CI [0.024, 0.126]). The measurement model demonstrated acceptable fit indices (χ²/df = 2.661; RMSEA = 0.059; CFI = 0.943; TLI = 0.932).DiscussionThese results highlight the importance of self-efficacy and psychological resilience as fundamental factors that promote life satisfaction among university student athletes. The study suggests that sports environments can enhance life satisfaction by strengthening both physical and psychological resources. Based on these findings, developing intervention programs aimed at improving self-efficacy and psychological resilience may significantly contribute to the well-being and satisfaction of student athletes.